Routability-aware Packing for High-density Nonvolatile FPGAs - Zheng, Huichuan; Xiong, Yuqing; Zuo, Jian; Zhang, Hao; Jia, Zhenge; Zhao, Mengying (2025 62nd ACM/IEEE Design Automation Conference (DAC), 2025)
Nonvolatile field-programmable gate arrays (NVFPGAs) can use multi-level cell (MLC) nonvolatile memories (NVMs) to enhance their logic density. However, the highdensity design of NVFPGAs degrades the intra-routability of configurable logic blocks (CLBs), which significantly prolongs the time consumed by the packing process in the computer-aided design (CAD) flow. To relieve the efficiency degradation, in this paper, we propose a routability-aware re-pair stage to adjust the logical-physical look-up table (LUT) assignments to mitigate the congestion and improve their intra-routability, thereby reducing the packing time. In addition, exploiting the structural equivalence of MLC LUTs, we remove unnecessary intra-routing attempts from packing to further improve efficiency. Evaluation shows the proposed strategies reduce packing time by 41.48 % on average. Index Terms-nonvolatile memory (NVM), multi-level cell (MLC), field-programmable gate array (FPGA), computer-aided design (CAD), packing.